Genetic analysis of morpho-physiological traits and yield components in F2 partial diallel crosses of bread wheat (Triticum aestivum L.) (2017)
Wheat breeding in the semi-arid region of Algeria aims to develop new cultivars combining high productivity and good abiotic stress tolerance. Therefore, it is essential to understand the mode of gene effects implicated in the genetic control of these characteristics. Nine parents of bread wheat and twenty derived F2 hybrid populations developed in a partial diallel scheme were evaluated with three replications at the experimental site of the National Agronomic Research Institute of Algeria (INRAA), Setif unit, during the 2012-2013 crop season. Results of the diallel analysis, indicated that the components associated with additive effects were more relevant than those associated with the dominance effects for most of the studied traits. Based on the proportion between dominant and recessive genes in all parents, the dominant alleles were present in greater frequency in group 1. Values of the gene proportion with positive and negative effects in the parents revealed an unequal distribution of dominant genes in the parents for almost all the traits except for chlorophyll content and grain number per spike which showed a symmetric distribution. The average degree of dominance indicated over-dominance for most of traits, suggesting that selection for these traits, in early generation, will be less efficient.Key words: genetic parameters, inheritance, selection, semi-arid, yield.